2013
DOI: 10.1007/s10151-013-1099-3
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous carcinoma of the rectum: a distinct clinicopathological entity

Abstract: Purpose The definition of mucinous tumours relies on quantification of the amount of mucus produced by neoplastic cells within the rectum. This has changed over the years to include varying degrees of mucin production. The inconsistency of diagnosis has led to conflicting reports in the literature regarding clinical outcomes and treatment response. A universally accepted definition and improved imaging and surgical techniques in the last decade are now challenging the traditional view of these tumours. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…The most common CRC histologic subtypes include adenocarcinoma, mucinous, signet ring cell, medullary, and micropapillary, however there are other rare histopathological variants [1]. The mucinous subtype accounts for 5% to 20% of all CRCs [2], and has been defined by the presence of abundant extracellular mucous which contributes to more than 50% of tumor volume [3]. …”
Section: Introductionmentioning
confidence: 99%
“…The most common CRC histologic subtypes include adenocarcinoma, mucinous, signet ring cell, medullary, and micropapillary, however there are other rare histopathological variants [1]. The mucinous subtype accounts for 5% to 20% of all CRCs [2], and has been defined by the presence of abundant extracellular mucous which contributes to more than 50% of tumor volume [3]. …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Mucinous carcinoma (MC) represents a subtype of rectal carcinoma; it is defined by high signal intensity in T 2 weighted (T2w) imaging, which identifies mucin pools in rectal carcinomas with a high accuracy. [10][11][12][13][14] Most studies have found that patients with MC have a poorer prognosis than those with non-mucinous (NMC) rectal cancer, [15][16][17][18] although some studies found no correlation between mucinous histotype and prognosis. 19,20 Recently, Hugen et al 21 performed a large population-based study in which multivariate analysis showed no differences in overall survival in MC and NMC except when the tumour was located in the rectum.…”
Section: Introductionmentioning
confidence: 99%
“…Mucinous carcinoma is diagnosed if the tumor cells produce mucin that aggregates into pools or lakes, occupying > 50% of the tumor [25]. As the definition of mucinous carcinoma has varied according to the amount of mucus produced by neoplastic cells within the rectum over the years, mucinous tumors of the rectum are less well understood than non-mucinous tumors [10]. Several studies have observed that mucin has a pressure effect that causes dissemination of cancer cells into the peritoneal cavity [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Hyngstrom et al [9] found that muci-nous cancer located in the rectum showed worse survival outcomes with a hazard ratio (HR) of death of 1.22, but not for those located in the colon (HR, 1.03). Chand et al [10] explained that mucinous carcinoma in the rectum has a more aggressive behavior than mucinous carcinoma in the colon because of the anatomical location and the immediate effect of the narrow pelvic cavity. In the present study, the association between the mucinous histologic type and open conversion in low colorectal cancer can be explained by the unique clinicopathologic behavior of mucin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation